(untitled) (Proceeding of the International Conference on Arts and Humanities, 2019)
The success rate of international brands in the global market is affected by many factors, one of the most important of which is culture. These days, advertisements which can be adapted to meet the cultural needs of the community will be far more effective. Therefore, the researchers have studied three international outdoor advertising in Iran contributed to cultural differences from the perspective of Hall and Hofstede cultural theories. In the process of this research, which is considered Quasi-quantitative, a questionnaire was developed based on the indexes of the Hofstede and Hall models and filled in by marketing and visual communication specialists. The results indicate that “Clear” in the "indulgence" and "power distance" indicators of the Hofstede model and "non-verbal communication" indicator of the Hall model had a score higher than 5 and L’Oréal had the highest score of 5.66 in the Hall model of "being". Signal, was able to score 5.08 and 5.06 in Hofstede’s dimension of "collectivism" and Hall’s dimension of "indirectness", respectively. The results show that “Clear” follow the Hall and Hofstede models more than two other brands and "being" and "femininity" are the indicators which are considered more than other indicators in advertisements of all three brands.